Development and efficacy testing of broad alphavirus vaccines and antivirals and characterization of alphavirus neuroinvasion - Rico, Amber, author; Olson, Ken, advisor; Ebel, Greg, committee member; Powers, Ann, committee member; Bowen, Richard, committee member; Chen, Chaoping, committee member (Colorado State University. Libraries, 2016)
Alphaviruses are mosquito-borne pathogens that cause worldwide disease and death in humans and animals. Several alphaviruses are select agents and are a legitimate biosafety and bioweapon concern. Additionally, several alphaviruses are emerging infectious diseases. Climate change and urbanization have expanded mosquito populations and increased human-mosquito interactions within this decade and will continue into future decades. As mosquito populations expand, naïve human populations are exposed to arthropod-borne viruses, including alphaviruses, and vector-borne diseases have surged. The increasing prevalence of arthropod-borne disease has highlighted the global need to develop measures that prevent or treat arthropod-borne disease infection. Currently, vaccines to prevent alphavirus infection are limited to investigational new drug status and no therapeutics are available to treat alphavirus disease. This dissertation will describe projects aimed at preventing or treating alphavirus infection and characterizing the process of alphavirus neuroinvasion. To address the concern of potential outbreaks of an intentional or natural nature, alphavirus vaccines based on the ectodomain of alphavirus E1 were designed and tested. Cationic liposomes complexed with nucleic acid adjuvants and alphavirus E1 protein (lipid-antigen-nucleic acid complexes; LANACs) provided the best platform for alphavirus E1 vaccination. Interestingly, western equine encephalitis virus (WEEV) E1 (LANAC WEEV E1) protected against both mouse WEEV and eastern equine encephalitis virus (EEEV) challenge but not Venezuelan equine encephalitis virus (VEEV); whereas, VEEV E1 (LANAC VEEV E1) protected against both VEEV and EEEV challenge but not WEEV. LANAC VEEV E1 + WEEV E1 vaccination protected mice against EEEV, VEEV, and WEEV challenge. Mice immunized with LANACs (LANAC WEEV E1, LANAC VEEV E1 or LANAC VEEV E1 + WEEV E1) mounted strong humoral immune responses, but were lacking neutralizing antibody. Hamsters immunized with LANAC WEEV E1 failed to mount humoral immune responses and were not protected from challenge. Antibody derived from E1 vaccination binds infected cells and purified E1, but not intact virions. E1 antibody is non-neutralizing yet protective against CHIIKV, EEEV, SINV, VEEV, and WEEV in vitro. In vivo we have demonstrated that antibody is protective against all three new world alphaviruses (NWAs0. Antibody affects late stages of the viral life cycle and likely inhibits virus release or cell death. Following a screen, conducted by our collaborators, of FDA approved and ex-US approved compounds for effectiveness against viral encephalitic and hemorrhagic fever viruses, we tested compounds for anti-alphavirus activity to develop therapeutics to treat alphavirus infection. Yield reduction assays identified four compounds that inhibited virus replication by two to four logs. These compounds were further tested in vitro for mechanism of action. Compounds P-75802, P-75803, P-75805, and P-75811 affected early stages of replication. Compound P-75802 was tested in vivo and was found to possess limited antiviral activity. The process of alphavirus neuroinvasion, particularly following peripheral inoculation, is poorly defined. In the studies described here, encephalitic alphavirus neuroinvasion following EEEV, VEEV, and WEEV intranasal and subcutaneous inoculation were described relying on bioluminescent in vivo and ex vivo imaging, CLARITY imaging, and histopathology. We found that neuroinvasion occurs through two routes dependent on inoculation method. The cranial nerves, particularly the olfactory tract nerve, were involved in neuroinvasion following intranasal inoculation. Neuroinvasion from the periphery, footpad inoculation, occurred via a route independent of the olfactory tract. Neuroinvasion occurred in areas where the blood brain barrier is naturally absent including the hypothalamus, anterioventral third ventricle region (AV3V), area postrema, and the pineal body.